REALISTIC MATHEMATICS LEARNING TO TEACH NEGATIVE NUMBER COUNTING OPERATIONS - Rosiah Juliati Pulukadang (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
Abstract The objective of this study is to investigate the impact of incorporating actual mathematics learning on student academic achievement in the domain of whole numbers. The present study employs a Posttest-Only Control Group Design for the purpose of conducting research. The participants of this study consist of two groups: class VII A, which serves as the experimental group and comprises 22 students, and class VII B, which serves as the control group and consists of 22 students. These groups were selected from SMP Negeri 6 Langowan during the 2022 academic year. The data collected were derived from the posttest outcomes in both the experimental and control groups. The experimental group exhibited an average learning outcome of 77.3, whereas the control group demonstrated an average learning outcome of 51.4. The normality test for the data is satisfied when the data follows a normal distribution. The data analysis yielded results with a significance level of 0.05, where the calculated t-value (tcount) was 7.1039, which is greater than the critical t-value (ttable) of 1.6819. The findings of this study indicate that students who employ a realistic mathematical approach to integer material exhibit superior learning outcomes compared to those who utilize standard learning methods.